1980
DOI: 10.1111/j.1151-2916.1980.tb10208.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Porous CaO Particles Formed by Decomposition of CaCO3 and Ca(OH)2 in Vacuum

Abstract: The solid products of decomposing CaCO, powder in vacuum at 510°C (sr-CaO) and of decomposing Ca(OH), powder at 320°C in vacuum (h-CaO) are particles which have approximately the same exterior dimensions as the parent CaCO, or Ca(OH), particles. N, adsorption and desorption isotherms show that srand h-CaO have high internal surface areas which for sr-CaO have cylindrical symmetry, with the most common diameters being -10 nm, and for h-CaO are slit-shaped, with the most common slit width being ~2 . 7 nm. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(35 citation statements)
references
References 14 publications
4
30
0
1
Order By: Relevance
“…While the distributions themselves were quite similar, the shape of the adsorption/desorption isotherms suggested a difference in the shape of the pores; c-CaO suggested the openings between packed spheres while h-CaO approximated slits or the gaps between plates when interpreted in accordance with Gregg and Sing (1982). This finding was in agreement with the pore structures suggested by Beruto et al (1980). Gullett and Bruce further reported that available porosity was filled by product more slowly for h-CaO, allowing a higher conversion to CaSO,, presumably due to this pore structure difference.…”
Section: Introductionsupporting
confidence: 89%
“…While the distributions themselves were quite similar, the shape of the adsorption/desorption isotherms suggested a difference in the shape of the pores; c-CaO suggested the openings between packed spheres while h-CaO approximated slits or the gaps between plates when interpreted in accordance with Gregg and Sing (1982). This finding was in agreement with the pore structures suggested by Beruto et al (1980). Gullett and Bruce further reported that available porosity was filled by product more slowly for h-CaO, allowing a higher conversion to CaSO,, presumably due to this pore structure difference.…”
Section: Introductionsupporting
confidence: 89%
“…4a) in which the degradation of the area of sample can be seen after the high-resolution study. The low stability of hydroxides under the high energy electron beam of the transmission electron microscopy has been reported by some authors [40,41]. Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Barret derived this relationship by assuming an adsorbed intermediate layer [4], Benito and Searcy [5] by assuming one of the diffusion steps of the gaseous product to be rate limiting. Cutler et al derived a similar expression [6] by postulating that, for calcium carbonate, CaO is first formed in some special activated form that occupies a constant fraction of the surface. Our derivation shows that no special assumption is necessary beyond that the reaction is reversible.…”
Section: K=w-rmentioning
confidence: 92%